A case report: intracoronary acetylcholine testing without a pacemaker may be one option in the left coronary artery. Issue 10 (20th October 2021) - Sueda, Shozo; Sakaue, Tomoki
Abstract: Background: The intracoronary acetylcholine (ACh) and ergonovine (ER) test is employed as a pharmacological spasm provocation test. ACh causes vasoconstriction in patients with coronary endothelial dysfunction such as coronary atherosclerosis, while ER induces coronary vasoconstriction through the activation of coronary smooth muscle. Case summary: An 84-year-old Japanese man was admitted to our hospital due to resting angina and syncope. Computed tomography coronary angiography (CTCAG) revealed severe proximal left anterior descending (LAD) coronary artery stenosis, but hybrid images of CTCAG and thallium-adenosine myocardial scintigraphy revealed no ischaemia. During syncope, inverted T waves on V5, V6 leads were recognized. After coronary arteriography, mild atherosclerotic stenosis (50%) was found at the proximal LAD artery, and we administered intracoronary ER 104 µg and 80 µg into the left and right coronary arteries because of suspected coronary spasm. However, no provoked spasm was obtained in either vessel. We administered 20, 50, and 100 µg intracoronary ACh into the left coronary artery (LCA) for 30 s without a pacemaker, because neither bradycardia nor cardiac arrest has occurred. Diffuse distal spasm was provoked after the administration of 100 µg ACh and the patient complained of typical chest pain and prodrome before syncope. The patient was diagnosed with coronary spastic angina by the ACh test but not the ER test. Discussion: Different coronary responses between ACh and ER were observed in this case. Intracoronary ACh testing without a pacemaker may be one option in the LCA if no bradycardia or arrest occurs.